Model to evaluate and optimise sustainability performance of customisable product service systems. (2018) - Wijekoon, Ken; Huang, Aihua; Badurdeen, Fazleena
Product service systems (PSS) are an integrated combination of products and services as opposed to products only. PSS can potentially become a more sustainable alternative to selling products for ownership by customers as, with PSS, producers retain ownership of the products across its life cycle. Currently, however, there are no frameworks or tools available to design and optimise PSS considering economic, environmental and societal sustainability and all life cycle stages simultaneously. To fill this gap, this paper presents a new methodology to evaluate and optimise sustainability of customisable PSS throughout total life cycle stages while economic, environmental and societal constraints are satisfied. A modular product where customisation can be achieved by selecting from alternative components is considered. Alternative approaches are developed to demonstrate the proposed methodology using a simple hypothetical example.